The Influence Of Financial Knowledge, Financial Attitude Dan Locus Of Control On Financial Behavior Of E-Wallet Users In Jakarta - Adiputra, I Gede; Suprastha, Nyoman; Tania, Levana (The journal of contemporary issues in business and government, 2021)
This study aims to analyze the influence of financial knowledge, financial attitude and locus of control on financial behavior. This study uses primary data obtained through a questionnaire that has been distributed directly and indirectly (via social media). The population in this study is the community of server-based electronic money users or commonly known as e-wallets who already have personal income, and are domiciled in Jakarta. The sample of this study is 201 respondents who are collected using non- probability methods with convenience sampling technique. The data that has been obtained is processed by PLS-SEM using the SmartPLS version 3.2.8 software. The findings of this study indicate that financial knowledge, financial attitude and locus of control have a significant effect on financial behavior.